2010
DOI: 10.1111/j.1528-1167.2010.02544.x
|View full text |Cite
|
Sign up to set email alerts
|

Alterations of intracerebral γ‐aminobutyric acid (GABA) levels by titration with levetiracetam in patients with focal epilepsies

Abstract: SUMMARYPurpose: The objective of this study was to determine if levetiracetam (LEV) modulates brain c-aminobutyric acid (GABA) in patients with epilepsy. Methods: Occipital GABA was assessed by protein magnetic resonance spectroscopy ( 1 H-MRS) in 16 patients with focal epilepsy at baseline and following the initiation of oral administration of LEV as monotherapy. Responder profiles were calculated as percentage of baseline seizure frequency. Alterations of GABA/Cr (creatine) of baseline measurements compared … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
19
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(22 citation statements)
references
References 36 publications
(59 reference statements)
1
19
0
1
Order By: Relevance
“…Previous data revealed that antiepileptic drugs (AED) have an effect on brain metabolites in 1 H MRS. It has been shown that valproate induces changes in cerebral myoinositol and glutamine concentrations, whereas new AEDs may increase GABA levels in patients with epilepsy . Therefore, we divided the patients into two groups: one group included patients with valproate treatment, whereas the other group covered all patients who received any medication but no valproate.…”
Section: Methodsmentioning
confidence: 99%
“…Previous data revealed that antiepileptic drugs (AED) have an effect on brain metabolites in 1 H MRS. It has been shown that valproate induces changes in cerebral myoinositol and glutamine concentrations, whereas new AEDs may increase GABA levels in patients with epilepsy . Therefore, we divided the patients into two groups: one group included patients with valproate treatment, whereas the other group covered all patients who received any medication but no valproate.…”
Section: Methodsmentioning
confidence: 99%
“…Higher magnetic fields, on the other hand, provide increased spectral resolution making GABA quantifiable (Deelchand et al, 2010;Gambarota et al, 2009;Mekle et al, 2009;Oz et al, 2006). GABA concentrations were found to be affected by neurological disorders like epilepsy (Doelken et al, 2010;Goddard et al, 2001;Simister et al, 2003), schizophrenia (Yoon et al, 2010), depression (Sanacora et al, 2004) or substance abuse (Behar et al, 1999;Ke et al, 2004).…”
Section: Neurotransmitter Metabolismmentioning
confidence: 99%
“…There is a compelling literature implicating low GABA in epilepsy and documenting successful pharmacological interventions for seizure disorders that are effective via the modulation of GABA (Doelken, et al, 2010; Mueller, et al, 2001; Petroff, Behar, Mattson, & Rothman, 1996a; Petroff, Rothman, Behar, Hyder, & Mattson, 1999; Petroff, Rothman, Behar, & Mattson, 1996b)except (Simister, McLean, Barker, & Duncan, 2003, 2009). Low brain GABA levels were associated with poor seizure control in patients with complex partial seizures (Petroff, et al, 1996b).…”
Section: Translating To the Human Condition: In Vivo Gaba Mrs Studiesmentioning
confidence: 99%